2002
DOI: 10.1016/s0005-2728(02)00305-5
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial respiratory rates and activities of respiratory chain complexes correlate linearly with heteroplasmy of deleted mtDNA without threshold and independently of deletion size

Abstract: To clarify the importance of deleted protein and tRNA genes on the impairment of mitochondrial function, we performed a quantitative analysis of biochemical, genetic and morphological findings in skeletal muscles of 16 patients with single deletions and 5 patients with multiple deletions of mtDNA. Clinically, all patients showed chronic progressive external ophthalmoplegia (CPEO). The size of deletions varied between 2.5 and 9 kb, and heteroplasmy between 31% and 94%. In patients with single deletions, the cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 58 publications
2
50
0
1
Order By: Relevance
“…All patients with single, large‐scale mtDNA deletions assessed in this study showed a combined complex I and IV deficiency, consistent with the removal of several mt‐encoded structural subunits and mt‐tRNAs, as previously reported 18, 20, 22, 33. However, 3 distinct respiratory chain profiles were observed, suggesting differential rates of COX‐I and NDUFB8 decline.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…All patients with single, large‐scale mtDNA deletions assessed in this study showed a combined complex I and IV deficiency, consistent with the removal of several mt‐encoded structural subunits and mt‐tRNAs, as previously reported 18, 20, 22, 33. However, 3 distinct respiratory chain profiles were observed, suggesting differential rates of COX‐I and NDUFB8 decline.…”
Section: Discussionsupporting
confidence: 89%
“…Larger mtDNA deletions have been associated with more severe disease and earlier disease onset 15, 16, 17, 18, 19. Whereas a highly significant,20 significant,15, 16, 21, 22 weak,18, 23 or no24 correlation has been reported between the percentage of COX‐deficient fibers and the degree of mtDNA heteroplasmy, most studies found no correlation between the biochemical defects and the nature of the deletion (the number of protein‐encoding genes and the complexes affected by the deletion) or deletion size alone 4, 15, 20, 22, 25. Interestingly, a higher proportion of COX‐deficient ragged‐red fibers was found in patients with deletions encompassing the 3 mtDNA‐encoded COX genes,26, 27 whereas an isolated complex I deficiency was reported in patients with smaller mtDNA deletions removing only complex I genes 26…”
mentioning
confidence: 99%
“…Single mtDNA deletions cause KSS, CPEO, or PS, whose affected tissues show impaired electron transport activity, ATP production, and mitochondrial protein synthesis [26,56,57]. Muscle biopsies from patients with KSS or CPEO show ragged-red fibers and cytochrome oxidase-negative fibers [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…The combined COX/SDH histochemical method enables the visualization of cells with mitochondrial dysfunction. This technique, with early studies dating back to 1968, remains popular, with many considering it the "gold standard" for identifying mitochondrial diseases in patients 14,19,26,27 . It is now frequently used to investigate mtDNA mutation-driven aging and aging-related disorders 12,13,18,20,21,24 .…”
Section: Figure 1 Mitochondrial Respiratory Complexes I-vmentioning
confidence: 99%